2020
DOI: 10.1186/s12891-020-3039-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic widespread pain on health status and long-term health predictors: a general population cohort study

Abstract: Background Chronic widespread pain (CWP) has a negative impact on health status, but results have varied regarding gender-related differences and reported health status. The aim was to study the impact of CWP on health status in women and men aged 35–54 years in a sample of the general population. The aim was further to investigate lifestyle-related predictors of better health status in those with CWP in a 12- and 21-year perspective. Method A gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…This is in line with evidence showing that men seem to recover, ie transit from chronic widespread pain to less spatially distributed pain, to a greater extent than women according to a longitudinal study. 26 The reasons for more WSP in women are unclear and multiple and possibly interacting factors (eg biological, psychosocial and cultural factors including gender roles) are probably involved. 21,25 The present study also found that individuals with the most WSP were more frequently born outside of Europe, had lower education levels and more health-care seeking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with evidence showing that men seem to recover, ie transit from chronic widespread pain to less spatially distributed pain, to a greater extent than women according to a longitudinal study. 26 The reasons for more WSP in women are unclear and multiple and possibly interacting factors (eg biological, psychosocial and cultural factors including gender roles) are probably involved. 21,25 The present study also found that individuals with the most WSP were more frequently born outside of Europe, had lower education levels and more health-care seeking.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Prospective studies in the general population have shown that localized pain (LP) can transition into WSP over time and vice versa, with men being less prone to develop persistent WSP. 26,27 In specialist settings (representing a selection of the most severe cases), smaller cohorts of chronic pain patients have been studied and WSP has been shown to be associated with a longer duration of pain. 28 To the best of our knowledge, no studies have investigated spreading of pain in large cohort studies in specialist settings.…”
Section: Introductionmentioning
confidence: 99%
“…Stress had the strongest negative effect on mental HRQOL, and pain was one of the variables with a strong negative effect on physical HRQOL. Pain is a common health problem and a may be a signi cant burden that in uences both parents and their families in different ways [12,49]. We found a high prevalence of persistent pain (> 3 moths) in the parents.…”
Section: Discussionmentioning
confidence: 64%
“…Still, the results indicate that the interplay of unemployment and a high number of pain sites before MMRP was associated with being on full-time sick leave 1 year after MMRP for men. Previous research has found that widespread pain causes the same worsening of health status for both men and women [46] and is associated with longterm sick leave [47]. Furthermore, results from a longitudinal follow-up study [46] revealed that men recovered from widespread pain to a greater extent than women.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has found that widespread pain causes the same worsening of health status for both men and women [46] and is associated with longterm sick leave [47]. Furthermore, results from a longitudinal follow-up study [46] revealed that men recovered from widespread pain to a greater extent than women. More women than men participate in MMRP [22,36] and most of the studies on MMRP are based on a majority of women.…”
Section: Discussionmentioning
confidence: 90%